RASIONALITAS MAHASISWI DALAM MEMILIH JURUSAN TEKNIK MESIN DI UNIVERSITAS RIAU - Sihotang, Tiolina; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was did in Faculity of Engineering University of Riau. This aims to knowing social perception (family, friends) of gender role as female students in mechanical engineering major and to knowing female students rationality of faculity of engineering doing their every single role as students in mechanical engineering major. This study entitled Rasionality of Female Students in Choosing Mechanical Engineering Major in University of Riau. This study was started from September 2016 until April 2017. The date collection technique is using sampling technique amount to 7 persons. The result of this study indicate that rasionality of female students in choosing mechanical engineering major because of the many job opportunities for mechanical engineering graduates. Rasionality of female students in doing their every single role is adaptation to around the majority of male, such as respect each other, unselfish, and help each other. Family and friends perception of female students who choose mechanical engineering major are reasonable as long as female students able to do their every single role and able to protect themselves from majority of male.Keywords : Rationality, Female Students, Mechanical Engineerin